2010
DOI: 10.1111/j.1463-1318.2009.01878.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of faecal incontinence in adults aged 30 years or more in general population

Abstract: Faecal incontinence is a common problem. Only a minority had reported this symptom to their physician and surprisingly few had received treatment for it. General awareness of faecal incontinence and treatment options should be improved among primary care physicians and general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 16 publications
1
32
2
1
Order By: Relevance
“…Chen et al reported a 35% prevalence for liquid stool and 22% solid stool incontinence in morbidly obese women [21]. These prevalences are much higher than studies in general populations which have documented a 12 and 9% prevalence of fecal incontinence in women and men, respectively [6,22]. It is unknown why morbidly obese women have such a high prevalence of fecal incontinence; previously suggested mechanisms include increased intra-abdominal pressure or peripheral neuropathy [7].…”
Section: Discussionmentioning
confidence: 90%
“…Chen et al reported a 35% prevalence for liquid stool and 22% solid stool incontinence in morbidly obese women [21]. These prevalences are much higher than studies in general populations which have documented a 12 and 9% prevalence of fecal incontinence in women and men, respectively [6,22]. It is unknown why morbidly obese women have such a high prevalence of fecal incontinence; previously suggested mechanisms include increased intra-abdominal pressure or peripheral neuropathy [7].…”
Section: Discussionmentioning
confidence: 90%
“…there was wide variation in specific factors assessed and the way that associations were determined, with some studies reporting univariate analyses alone and other studies reporting results of multivariate modeling. overall, the 3 most commonly reported factors associated with fi were increasing age, 4,14-16,18,23-25,30,36,39,42 diarrhea and/or fecal urgency, [14][15][16]18,19,24,27,41 and urinary incontinence and/or overactive bladder 13,14,17,18,21,25,32,39 (table 4). the 3 most commonly reported factors not associated with fi were obstetric history or previous obstetric trauma, [13][14][15]18,21,32,36 sex, 14,16,27,40,42 and constipation and/or hard stools 15,16,18,19 (table 4).…”
Section: Prevalence Estimates For Fimentioning
confidence: 99%
“…overall, there were only 3 studies meeting 4 or more of the high-quality criteria that investigated the prevalence of fi among a representative sample of adult community dwellers, that is, among men and women aged ≥18 years. 12,14,16 Study Aims and Design of the 32 studies reporting a prevalence of fi, 12 studies had the primary aim of determining the community prevalence of fi in isolation, [12][13][14][15][16][17][18][19][20][21]23,29 whereas 13 studies investigated prevalence of fi in combination with rates of urinary incontinence, 24 35 and 2 studies aimed to correlate rates of incontinence with mortality 30 and functional status 26 ; in each of these latter studies, prevalence rates of fi were reported as a secondary outcome measure. all of the studies were population-based, cross-sectional studies, except for 1 study performed by adolfsson et al, 37 which was a case-control study.…”
Section: Studies Reporting Prevalence Of Fimentioning
confidence: 99%
“…AI is therefore affected by low rates of self-reporting and therapy-seeking behavior [20]. In this respect, Aitola et al , studying 162 subjects who reported episodes of bowel incontinence at least twice a month, showed that only 27% of cases had discussed the problem with their primary physician and only 10% had received treatment for the problem [21]. When questioned, 66% responded that they felt that they actually needed treatment, if it was available.…”
Section: Prevalence Of Anal Incontinencementioning
confidence: 99%